PENGARUH MODEL INDEX CARD MATCH TERHADAP HASIL BELAJAR AKIDAH AKHLAK KELAS II MI NU SUKOMALO LAMONGAN - Fithriyah, Musa'adatul; Viyanti, Pratiwi; Muiz, Abdul (STIT Ibnu Rusyd Tanah Grogot, 2024)
The low student learning outcomes in Aqidah Akhlak lessons are due to the learning model used which tends to be teacher-centered with a lecture model, therefore innovative learning models are needed to be an alternative problem solving for low student learning outcomes, one of which is by applying the Index Card Match model. This study aims to determine the effect of the Index Card Match model on the Akidah Akhlak learning outcomes of grade II students of MI NU Sukomalo Lamongan. The type of research method used is quantitative research. The research design used is One Group Pre-Test Post-Test Design, in this design there are accurate results by comparing the learning outcomes of the situation before and after being given treatment with the Index Card Match model. Data analysis techniques use differentiation, difficulty and sensitivity of question items. This study uses a paired sample t-test with a significance level of less than 0.05. The results showed a sig value of 0.000 which means less than 0.05 so it can be stated that H0 is rejected and Ha is accepted. Thus obtaining information that there is an effect of the Index Card Match model on the learning outcomes of Akidah Akhlak class II at MI NU Sukomalo Lamongan and the average learning outcomes of students show before using the Index Card Match model the average value is 56.35 and after using the Index Card Match model the average value is 82.3 that there is an increase in student learning outcomes by 25.95. Based on the explanation of the research results as a whole, it can be concluded that there is an influence and improvement in student learning outcomes after being treated with the Index Card Match model on the learning outcomes of Akidah Akhlak class II at MI NU Sukomalo Lamongan.